Emodin-nicotinamide (1:2) cocrystal identified by thermal screening to improve emodin solubility - Park, Boosung; Yoon, Woojin; Yun, Jungmin; Ban, Eunmi; Yun, Hoseop; Kim, Aeri (International Journal of Pharmaceutics, 2019)
Emodin (EM), an anthraquinone obtained from natural products, is known for many pharmacological activities. However, further evaluation and interpretation of toxicity or pharmacological activity of emodin are limited due to its poor aqueous solubility. We aimed to identify an emodin cocrystal with improved pharmaceutical properties. Among various compounds screened by thermal analysis, nicotinamide (NCT) was identified as a potential cocrystal coformer, based on the presence of an exothermal peak in DSC profiles of the physical mixture of EM and NCT. Crystallization of EM-NCT cocrystal (EM-NCT) using slow or rapid solvent evaporation method yielded a novel cocrystal at 1:2 ratio. Single crystal structure analysis revealed EM dimers and NCT tetramers connected alternatively via H-bonds to make one-dimensional chains which are joined by inter-chain H-bonds between NCT to form two-dimensional layers. The EM molecules are planar with intramolecular H-bonds between O atoms. Compared with EM, the EM-NCT cocrystal showed improved aqueous solubility, dissolution rate, and stability. Hence, EM-NCT cocrystal is proposed as a more suitable solid form for further development as pharmaceutical products.
Keywords: Crystallization; Emodin; Hot Temperature; Niacinamide; Solubility; Cocrystal; Emodin; Hydrogen bonding; Nicotinamide; Single crystal structure; Solubility